Business ethics : an ethical decision-making approach - Schwartz, Mark S., 4 0 16; 5 (Malden, MA : Wiley Blackwell, 2017)
Business Ethics: An Ethical Decision-Making Approach presents a practical decision-making framework to aid in the identification, understanding, and resolution of complex ethical dilemmas in the workplace. -Focuses exclusively on three basic aspects of ethical decision making and behavior-how it actually takes place, how it should take place, and how it can be improved -Uses real-life examples of moral temptations and personal ethical dilemmas faced by employees and managers -Discusses the biases, psychological tendencies, moral rationalizations, and impact of self-interest as impediments to proper ethical decision making -Includes relevant examples of ethical misconduct and scandals appearing in the news media.
Title Page; Copyright; Acknowledgments; Introduction to Ethical Decision Making; Unethical Activity in Society; Unethical Activity in the Workplace; Major Corporate Ethical Scandals; An Ethical Decision-Making Approach to Business Ethics; About This Book; A Few Key Definitions; The Organization of the Book; Notes; References; Part One Descriptive Theory; Chapter one What Determines Ethical Behavior?; The Good or Bad Apple Approach to Ethical Decision Making; The Situational Approach to Ethical Decision Making; Chapter Summary; Notes; References;Chapter Two The Ethical Decision-Making ProcessEnvironmental Norms; Moral Awareness Stage; Moral Judgment Stage; Intention Stage; Moral Behavior Stage; Chapter Summary; Notes; References; Chapter Three Impediments to Proper Ethical Decision Making; Improper Framing; Cognitive Biases and Psychological Tendencies; Moral Rationalizations; Self-Interest; Chapter Summary; Notes; References; Part Two Normative Framework; Chapter Four Distinguishing Right from Wrong; Stage 1: Application of Moral Standards; Stage 2: The Public-Parent-Pillow (3P) Filter;Putting It All Together: A Normative Framework for Ethical Decision MakingChapter Summary; Notes; References; Chapter Five The Decision to Report Misconduct; How Does the Decision to Blow the Whistle Take Place?; Summary of Positions on the Morality of Reporting Misconduct; Proposed Criteria for External Whistleblowing; Proposed Criteria for Internal Whistleblowing; Application of Criteria; Chapter Summary; Notes; References; Part Two Normative Framework; Chapter Six Developing and Sustaining an Ethical Corporate Culture; First Pillar: Core Ethical Values; Second Pillar: Formal Ethics Program;Third Pillar: Ethical LeadershipOther Considerations to Sustaining an Ethical Corporate Culture; Chapter Summary; Notes; References; Chapter Seven What Would You Do? Common Workplace Dilemmas; Different Types of Ethical Situations; Pretending to be a Student to Get Competitive Information?; Disclose Leaving Firm for Graduate School?; Sending Emails to Boss's Personal Account?; Take Advantage of Firm's 25 Dinner Policy?; Disclose Impending Layoffs?; Let Manager Take Credit for Your Analysis?; Disclose Mistake to Manager and Client?; Say Something When Boss Exaggerates Your Resume?;Report Friend with Substance Abuse Problems?Hire Son of Important Client?; Post Rave Reviews for Product on Internet?; Summary of the Ethical Dilemmas; Chapter Summary; Notes; References; Conclusion Navigating the Moral High Road; Implications for the Integrated and Multifaceted Ethical Decision-Making Models; Key Recommendations and Takeaways; Final Thoughts; Notes; References; Appendix A Factors Affecting Moral Character; Notes; References; Appendix B Descriptive Ethical Decision-Making Models; Notes; References; Appendix C Normative Ethical Decision-Making Models; Notes; References
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 23, 2017).
Keywords: 2 -- 0; 6; Business ethics. -- 20; 20; Electronic books. -- 2